Real scale simulation of ballistic test for soft armor - Dippolito, Mario (Kansas State University, 2017)
The strength of the fabric system is based on fiber strength and fabric mechanics. Modeling a fabric system accurately requires research into fiber behavior within the yarn and yarn behavior within the fabric. Limited computer resources require new approaches to yarn modeling and fabric modeling especially in regards to ballistic impact. The fabric is discontinuous. There are many factors which require modeling the physics in order to accurately simulate and design fabric systems. Weaving yarns into fabrics can introduce fiber level damages such as surface defects and crimps through sliding friction and bending and thus add variance to the tensile strength of the fibered yarn. A Weibull distribution is an often used method to develop a statistical model and is developed to calculate the strength of the yarn. It is necessary to carefully remove the fibers from the as woven fabric and use a standard ASTM single fiber tensile test to create a Weibull distribution of tensile strength. In general in Kevlar systems the edge radius for laboratory projectiles is much larger than the actual dimeter of the fiber; however, the yarn itself can be sheared, and this fibered yarn system requires modeling. There is no direct measurement of Kevlar fiber shear strength, so combined tensile-twist test data is used to develop equations to determined shear strength. DFMA is modeling software developed to create digital fabrics in a method that accurately models yarn shape with limited computer resources using a concept of a digital fiber. The digital fiber represents multiple real fibers, so it is necessary to use the digital yarn effective bending rigidity developed with numerical simulation of experimental results. Since the yarn is composed of hundreds to thousands of fibers, the physical yarn cannot be modeled in full scale fabrics. The yarn composed of digital fibers is structurally similar to real yarns and is capable of representing the real fabric mechanics. In the process of impact, within the relatively short time frame, the distribution of stress is mostly in principal yarns at a time when the event is considered complete through penetration or projectile rebound. The hybrid mesh method represents the small number of principal yarns with high density mesh and the rest of the fabric (the non-principal yarns) with coarse mesh. With hybrid mesh, the full scale simulation of actual fabrics is possible. The projectile geometry for real threats is variant depending on the types of projectiles in use (projectiles for maximum energy transfer to the target or projectiles for high shear). The laboratory projectiles are therefore variant in order to represent threats. In this research the RCC is the threat and two standard weights are modeled with local geometry. The local laboratory projectile geometry is controlled however it is bounded by a tolerance much larger than the Kevlar fibers studied here. It does act against the fibered yarn which will shear mechanically dependent on fiber to fiber interactions and possibly fiber shear strength.
Keywords: digital element analysis, textile mechanics, ballistic strength, inter-fiber friction, RCC